(untitled) (Intent Research Scientific Journal, 2023)
In this article, we will explore the importance of fostering a positive attitude towards men in raising girls. We discuss the methods that parents and caregivers can use to develop a positive attitude towards men and present the results of studies that show the benefits of such relationships, and finally, we offer suggestions on ways to promote a positive attitude towards men in raising girls.